The association between mid-facial morphology and climate in northeast Europe differs from that in north Asia: Implications for understanding the morphology of Late Pleistocene Homo sapiens. Issue 107 (June 2017) - Evteev, Andrej A.; Movsesian, Alla A.; Grosheva, Alexandra N.
Abstract: The climate of northeastern Europe is likely to resemble in many ways Late Pleistocene periglacial conditions in Europe, but there have been relatively few studies exploring the association between climate and morphology in the mid-face of modern northeastern European populations. To fill this gap, we sampled 540 male skulls from 22 European and Near Eastern groups, including 314 skulls from 11 populations from northeastern Europe, to test for possible climate-morphology association at the continental scale. Our results found a moderate and highly significant association (R = 0.48, p = 0.0013, Mantel test) between sets of 23 mid-facial measurements and eight climatic variables. A partial least squares analysis revealed this association to be mostly driven by differences between groups from northeastern Europe and populations from the Mediterranean and the Caucasus. Matrices of between-group genetic distances based on Y-chromosome and mtDNA markers, as well as cranial non-metric and geographic distance matrices, were used to control for the possible influence of shared population history. Irrespective of which measure of neutral between-population distances is taken into account, the association between cranial variables and climate remains significant. The pattern of association between climate and morphology of the mid-face in western Eurasia was then compared to that in east and north Asia. Although differences between the two were found, there were also similarities that support existing functional interpretations of morphology for the bony parts of the upper airways. Last, in a preliminary analysis using a reduced set of measurements, mid-facial morphology of several Upper Paleolithic European Homo sapiens specimens was found to be more similar to groups from northern and northeastern Europe than to southern European populations. Thus, the population of northeastern Europe rather than east and north Asian groups should be used as a model when studying climate-mediated mid-facial morphology of Upper Paleolithic European H . sapiens .